Pattern of Use of Highly Active Antiretroviral Therapy Regimens and Pattern of Occurrence of Adverse Drug Reactions in an Indian Human Immunodeficiency Virus Positive Patients - Radhakrishnan Rajesh; Sudha Vidyasagar; Danturulu Muralidhar Varma; Anand Naik; Brahmavar Mohandas Hegde; Vasudeva Guddattu; Asha Kamath (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Background: In India, Human immunodeficiency (HIV) infected patients with highly active antiretroviral therapy (HAART) are at higher risk of developing adverse drug reactions (ADRs). Objectives: The aim of this study was to characterize the pattern of use of HAART, occurrence, incidence, severity and causality of ADRs to HAART in Indian HIV positive patients. Methods: This was a prospective observational study conducted between August 2009 and May 2012. Enrolled HIV positive patients were intensively monitored for ADRs with fixed dose antiretroviral therapy as per National AIDS Control organization (NACO).World Health Organization (WHO) definition of ADR was adopted to detect ADRs to HAART and classified based on WHO adverse reaction terminologies. Naranjo’s scale was used for causality assessment of ADRs. Preventability was assessed using Thornton and Schuman criteria and severity was assessed using the modified Hart wig and Siegel scale. Pattern of ADRs was assessed with patient demographics, ADRs characteristics, and pattern of drug and reaction characteristics. P-value <0.05 was considered as statistically significant. Results: A total of 426 ADRs to HAART were evaluated from 1982 HIV positive patients during the study period. The overall incidence of ADRs to HAART was 21.4%. Significant difference was seen in the incidence of ADRs in the age group of 41-60 years (p <0.001), CD4+T-cell counts of 350-500 cells/µl (p <0.001), females (p <0.001). Three fatal ADRs of with cutaneous drug eruptions of Steven Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) was 1.1%. Anemia (31.7%) accounted for majority of the reports followed by vomiting (15.5%), skin rash (12.9%) and peripheral neuropathy (10.7%). The suspected drug was withdrawn for the management of the ADRs in majority (27.9%) of the reports. Higher incidence rate of ADRs was noted with lamivudine (3TC) + nevirapine (NVP) + stavudine (D4T) (22.9%). In, naranjo's causality assessment, majority of the ADR reports were rated as possible (69%). Symptomatic treatment for ADRs was given in 91.8% of the reports and 86.4% of the reports the patient recovered from the suspected adverse reaction at the time of evaluation. Conclusion: In India, occurrence of ADRs to HAART in HIV infected patients was found to be higher with zidovudine induced anemia (31.7%). The higher percentage of ADRs to HAART was seen with female patients, age 41-60 years; CD4+ T-cell counts 350-500 cells/µl. Physician must focus for monitoring all lab investigations for early detection and prevention of adverse effects associated with HAART.
Keywords: Human immunodeficiency virus